Migrating the Black body : the African diaspora and visual culture - Raiford, Leigh; Raphael-Hernandez, Heike (Book collections on Project MUSE., 2017)
Migrating the Black Body explores how visual media - from painting to photography, from global independent cinema to Hollywood movies, from posters and broadsides to digital media, from public art to graphic novels -has shaped diasporic imaginings of the individual and collective self. How is the travel of black bodies reflected in reciprocal black images? How is blackness forged and remade through diasporic visual encounters and reimagined through revisitations with the past? And how do visual technologies structure the way we see African subjects and subjectivity? This volume brings together an international group of scholars and artists who explore these questions in visual culture for the historical and contemporary African diaspora. Examining subjects as wide-ranging as the appearance of blackamoors in Russian and Swedish imperialist paintings, the appropriation of African and African American liberation images for Chinese Communist Party propaganda, and the role of YouTube videos in establishing connections between Ghana and its international diaspora, these essays investigate routes of migration, both voluntary and forced, stretching across space, place, and time.